2007
DOI: 10.1345/aph.1k270
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Potential Medication Problems Among Dually Eligible Older Adults in Medicaid Waiver Services

Abstract: Prevalence of potential medication problems in MSSP was markedly higher than reported in the original home healthcare sample used to test the Home Health Criteria. The prevalence rate for older adults at risk for nursing home placement necessitates expanded screening and medication therapy management interventions, especially upon initial enrollment and for those taking multiple medications. Interventions are needed to increase medication problem identification and resolution while promoting collaboration amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
1
13
2
Order By: Relevance
“…The proportion of patients with actual medication duplication in our study was lower than that reported in a study done in Australia (20%)[5], and in a study in California among elderly patients where 24.2% had unnecessary therapeutic duplication [11]. The populations in those studies were different from our study population.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The proportion of patients with actual medication duplication in our study was lower than that reported in a study done in Australia (20%)[5], and in a study in California among elderly patients where 24.2% had unnecessary therapeutic duplication [11]. The populations in those studies were different from our study population.…”
Section: Discussioncontrasting
confidence: 87%
“…Studies that have looked at home management of medicines found inappropriate practices in 10-57% of patients [5,7,8]. The factors that were associated with these practices included: gender, age, confusion between trade and generic names [9], education level [10] and number of medicines [11]. …”
Section: Introductionmentioning
confidence: 99%
“…The higher number of medication-related problems documented in our study compared to previous studies may be due to a several factors. 21, 23,24 First, previous assessments of medication use often target patients with specific chronic conditions or pre-defined quality indicators. We examined medication-related problems across all chronic and acute diseases, taking into account the whole person.…”
Section: Discussionmentioning
confidence: 99%
“…28 In a study of potential medication-related problems in dually eligible older adults in a Medicaid waiver management program, 49% were found to have at least one potential medication-related problem, with the most prevalent problem being therapeutic duplication, which occurred in 24% of individuals. 29 . A large pharmaceutical care registry between of patients cared for by pharmacists working in ambulatory care clinics and community pharmacy settings found that 30% of older adults had at least one drug therapy problem, with the most common problems being additional drug therapy needed (30%), too low dosage (23%), and nonadherence (18%).…”
Section: Discussionmentioning
confidence: 99%